A "Nation‐ized" Intersectional Analysis: The Politics of Transnational Campus Unity. Issue 157 (March 2017) - Okazawa‐Rey, Margo
Abstract : The author introduces the concept of "nation" as an analytic category in contemporary diversity discourse and intersectional analysis of social relations in U.S. higher educational institutions. She then suggests how an intersectional lens that includes nation can expand possibilities for understanding the experiences of international students and coalitions between them and students born and raised in the United States.